THE ANTECEDENTS OF ECOTOURISM INTENTION - Shania Vebiola Manihuruk; Luki Adiati Pratomo (Jurnal Ekonomi Trisakti, 2023)
Many people today need to pay more attention to the environment. In addition, more and more activities are making people unaware of how harmful their actions are to the environment. The aim is to examine the determinants influencing tourists' intentions to visit for ecotourism purposes. This study found a strong correlation between the three important factors determining tourists' interest in ecotourism sites. This is an environmental concern, the future time and eco-destination perspectives picture. This study also reports a strong relationship between eco-destination image, future time perspective, and environmental concern. This research is experimental research conducted in Indonesia. One hundred seventy-five respondents aged 20 to over 50 years were given a questionnaire to fill out to collect data. Purposive sampling was used as the sampling method in this study. The Structural Equation Model (SEM) approach assesses the research hypothesis. According to research, the contribution of time perspective to decision-making about visiting ecotourism sites is beneficial. Environmental concern also influences the intention to engage in ecotourism. It will increase ecological awareness if it has a positive reputation as an eco-friendly destination. If the image of an eco-friendly destination evokes pleasant emotions and attachments, the intention to visit ecotourism increases. Future research is expected to add more variables, such as loyalty. Further research can be carried out on other ecotourism destinations such as Tanjung Putting National Park, Kawah Ijen, Nusa Penida Island, etc.